Coaching psychology: an approach to practice for educational psychologists. Issue 3 (2nd July 2016) - Adams, Mark
Abstract: Coaching psychology is a distinct sub-discipline of academic and applied psychology that focuses on the enhancement of performance, development and well-being in the broader population. Applied in educational contexts, the practice of coaching psychology has the potential to have a positive impact by supporting children and adults to achieve enhanced standards of functioning and well-being. It therefore represents a way in which educational psychologists (EPs) might elect to diversify their practice. However, EPs are disproportionately under-represented in the development of this emerging field. This article charts the birth and evolution of contemporary coaching psychology, and presents a case study illustrating the application of this methodology in a school context. Suggestions are given regarding professional development activities that might be undertaken by EPs seeking to develop coaching psychology as a strand of their practice.